Transcranial direct current stimulation combined with physical exercise in rotator cuff tendinopathy: a protocol for a blinded randomised controlled trial - César Augusto Medeiros Silva; Clécio Gabriel de Souza; Vinicius Batista Lima; Hannely Beatriz Menezes Cosme; Romário Nóbrega Santos Fonseca; Fuad Ahmad Hazime; Rodrigo Scattone da Silva; Rodrigo Pegado de Abreu Freitas (BMJ Open)
Introduction Pain is one of the primary symptoms affecting individuals with rotator cuff tendinopathy. Physical exercise serves as the main approach for managing this condition, aiming to restore movement patterns, optimise scapular kinematics and improve strength and local muscular endurance. Pain neuromodulation techniques, such as transcranial direct current stimulation (tDCS), may offer complementary non-pharmacological options for pain relief by promoting central modulation and altering cortical excitability.Methods and analysis This protocol outlines a randomised, blinded clinical trial. Participants will be randomly allocated to two groups: G1 (active tDCS combined with progressive exercise) and G2 (sham tDCS combined with progressive exercise). The protocol will span 4 weeks, with two sessions per week. Pain intensity, measured using the numerical pain scale, will serve as the primary outcome. Secondary outcomes will include physical function, range of motion, global perception of change and treatment adherence.Ethics and dissemination This protocol was approved by the Ethics Committee Health Sciences College of Trairi, Federal University of Rio Grande do Norte (number: 6.821.408). Followed the Declaration of Helsinki recommendations for research with human beings. The results will be published later in peer-reviewed journals and scientific events.Trial registration number The Brazilian Registry of Clinical Trials (RBR-59xmv6s); Results.